(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
For the first time fossil macroscopic remains of charcoal as direct evidence of palaeo-wildfires from the Late Permian Gröden Formation of the Bletterbach-Butterloch area in Northern Italy is described. The charcoal consists of pycnoxylic wood and originates from gymnosperms, but a more specific affiliation is not possible due to the fragmentary nature of the material. On a global scale our knowledge about Late Permian fire-ecology is still rather scarce and this finding helps to fill one of the numerous geographical gaps in our current knowledge about Late Permian wildfires.